Parental Perception of Childhood Bruxism Three Years after the Covid-19 Pandemic - , Debora Matos de Medeiros; , Maria Eduarda Brito Lopes; , Kaio Henrique Soares; , Elida Lucia Ferreira Assuncao; , Patricia Furtado Goncalves; , Fabiola Belkiss Santos de Oliveira; , Julia Maria Moreira Santos (Archives of Current Research International, 2024)
Objective: To determine the frequency of child bruxism in the North of Minas Gerais three years after the pandemic period. Materials and Methods: This was a quantitative, cross-sectional, exploratory study with descriptive analysis involving parents/guardians of children aged 2-7 years. A total of 65 valid questionnaires were completed, containing questions about sociodemographic data, perception of clenching and teeth grinding, sleep quality, routine changes during Covid-19, and harmful habits. Results: The average age of the children was 4.2 years, with a higher frequency of children between 2-3 years old (24; 36.9%). Sleep bruxism was the most commonly noticed habit by parents (n=35; 55.8%), along with agitation (n=39) and mouth breathing (n=16) during the child's sleep. There was no significant change in bruxism observed due to Covid-19. Discussion: Bruxism is an oral parafunction that can compromise the health of the stomatognathic system and can be identified since childhood. In children, factors such as sleep disturbances and respiratory changes may be associated with bruxism. Stressors can also induce or exacerbate bruxism, although this was not observed in children after the pandemic. Conclusion: Parents/guardians of children aged 2-7 years who participated in the study noticed the presence of sleep bruxism in their children. However, an increase in childhood bruxism cannot be suggested three years after the COVID-19 pandemic.